Broadening international perspectives on the legal environment for personnel selection - MYORS, Brett (Institutional Knowledge at Singapore Management University, 2008)
Perspectives from 22 countries on aspects of the legal environment for selection are presented. Issues addressed include a) whether there are racial/ethnic/religious subgroups viewed as “disadvantaged minority”, b) whether research documents mean differences between groups on individual difference measures relevant to job performance, whether there are laws prohibiting discrimination against specific groups, d) what is required to make and refute a claim of discrimination, e) what are the consequences of violation of the laws, f) whether particular selection methods are limited or banned, g) whether preferential treatment of members of minority groups is permitted, and h) whether the practice of Industrial and Organizational psychology has been affected by the legal environment.